Internet Addiction Effect on Quality of Life: A Systematic Review and Meta-Analysis - Farzaneh Noroozi; Soheil Hassanipour; Fatemeh Eftekharian; Kumars Eisapareh; Mohammad Hossein Kaveh (The Scientific World Journal)
Purpose. Due to the use of different methodologies, tools, and measurements, the positive or negative impact of Internet use on human life quality is accompanied by a series of ambiguities and uncertainties. Therefore, in this study, a systematic review and meta-analysis are conducted regarding the effect of Internet addiction on the quality of life. Methods. A systematic search of resources was conducted to investigate the effect of Internet addiction on the quality of life. The databases of PubMed, Cochrane Library, Scopus, Web of Science, Embase, and Science Direct were searched from January 1980 to July 2020. The articles were screened by two researchers in multiple levels in terms of the title, abstract, and full-text; then, final studies that met the inclusion criteria were retrieved and included in the study. Results. After searching the previously mentioned international databases, 3863 papers were found, 18 of which we included in the final analysis. Surveys indicated that people who had a high Internet addiction received lower scores of quality of life than those who were normal Internet users (OR = 2.45, 95% CI; 2.31–2.61, p<0.001; I2 = 85.23%, p<0.001). Furthermore, There was a negative significant relationship between Internet addiction and quality of life in the psychological (OR = 0.56, 95% CI: 0.32–0.99, p=0.04, I2 = 97.47%, p<0.001), physical (OR = 0.58, 95% CI: 0.39–0.86, p=0.007, I2 = 95.29%, p=0.001), and overall quality of life score (OR = 0.39, 95% CI: 0.27–0.55, p<0.001, I2 = 0.0%, p=0.746). Conclusion. These findings illustrate that Internet addiction should be regarded as a major health concern and incorporated into health education and intervention initiatives.